Eddie's Psychological Problems in Mitch Albom's The Five People You Meet in Heaven - Muhammad Hafidz Hilmawan; Rahmawan Jatmiko (Universitas Gadjah Mada, 2019)
This research aims to understand the characterization of Eddie, as someone who lives a life full of psychological problems, in the novel The Five People You Meet in Heaven (Albom, 2003). This research examines all the psychological problems that Eddie has and analyzes the roots of all of them. Eddie’s journey in heaven after death where he meets five different people is seen as the way Eddie solves all the problems that he has. By employing Sigmund Freud’s psychoanalytic approach, this research focuses on the psychological problems that are most prevalent in Eddie’s character. The data are taken from the narratives and dialogues in the story. The background chapters in this novel are analyzed to understand the roots of Eddie’s psychological problems. His journey in heaven is viewed as the method of curing all of those problems.